Phenomenology of Large Nc QCD : Arizona State University, Tempe, USA, 9-11 January 2002 - Lebed, Richard F. (Proceedings from the Institute for Nuclear Theory, 2002)
The generalization of QCD from three to NC colors, developed in 1974 by Nobel laureate Gerard 't Hooft, has proved to be an extraordinarily useful and robust theoretical extension for studying the behavior of strong interaction physics. This book is the proceedings of the first-ever meeting exclusively devoted to large NC QCD. The workshop brought together representatives of many subdisciplines for a "meeting of minds" on topics ranging from finite temperature and density to the lattice, perturbative QCD, instantons, mesons, baryons, and nuclear physics. Beginning with 't Hooft's keynote presentation, the contributions are designed to introduce uses of large NC methods in each specialty to a broader particle physics audience.